Fibroblast growth factor 19 in patients with bile acid diarrhoea: a prospective comparison of FGF19 serum assay and SeHCAT retention. Issue 8 (27th August 2013) - Pattni, S. S.; Brydon, W. G.; Dew, T.; Johnston, I. M.; Nolan, J. D.; Srinivas, M.; Basumani, P.; Bardhan, K. D.; Walters, J. R. F.
Summary: Background: Bile acid diarrhoea is a common, under‐diagnosed cause of chronic watery diarrhoea, responding to specific treatment with bile acid sequestrants. We previously showed patients with bile acid diarrhoea have lower median levels compared with healthy controls, of the ileal hormone fibroblast growth factor 19 (FGF19), which regulates bile acid synthesis. Aim: To measure serum FGF19 and SeHCAT retention prospectively in patients with chronic diarrhoea. Methods: One hundred and fifty‐two consecutive patients were grouped according to 75 Se‐homocholic acid taurine (SeHCAT) 7‐day retention: normal (>15%) in 72 (47%) diarrhoea controls; ≤15% in 54 (36%) with primary bile acid diarrhoea, and in 26 (17%) with secondary bile acid diarrhoea. Fasting blood was assayed for FGF19, 7α‐hydroxy‐4‐cholesten‐3‐one (C4) and total bile acids. Results: FGF19 was significantly lower in the primary bile acid diarrhoea group compared with the diarrhoea control group (median 147 vs. 225 pg/mL, P  < 0.001), and also in the secondary group ( P  < 0.006). FGF19 and SeHCAT values were positively correlated ( r s  = 0.44, P  < 0.001); both were inversely related to C4. Other significant relationships included SeHCAT and body mass index (BMI)( P  = 0.02), and FGF19 with age ( P  < 0.01). The negative and positive predictive values of FGF19 ≤ 145 pg/mL for a SeHCAT <10% were 82% and 61%, respectively, and were generally improved in an index including BMI, age and C4. In a subset of 28 primary patients, limited data suggested that FGF19 could predict response to sequestrant therapy. Conclusions: Reduced fibroblast growth factor 19 is a feature of bile acid diarrhoea. Further studies will fully define its role in predicting the response of these patients to therapy.